Life Cycle Assessment Of Copper Recovery Process From Printed Circuit Boards - Kousalya, Subramaniam (2023)
E-waste becoming a global environmental concern. E-waste is considered as a waste from Electrical and Electronic Equipment (WEEE) refers to all discarded or end-of-life ICTs and other electronic/electrical equipment that requires an electrical current from an electromagnetic field (circuitry) in order to function. The amount of e-waste ending up in landfills increasing every year. Disposal management of e-waste is one of the biggest issues in this case where 80% of e-waste was ending up in landfills. The e-waste disposal to landfills will cause several impacts because generally it contains hazardous substances like lead, arsenic and mercury which is harmful to the environment and pose serious risks to human health. However, e-waste still contains other valuable materials that potentially can be recovered. This recovery process is known as urban mining. Thus, this study is to determine the environmental impact using life cycle assessment of copper recovery from e-waste. The GaBi software and Tool for the Reduction and Assessment of Chemical and Other Environmental Impacts known as TRACI 2.0 from US EPA was used to assess the environmental impact of recovery process. This study shows that urban mining having less impact compared to conventional mining in the aspect of Global Warming Potential (GWP), Acidification, Eutrophication, Ozone depletion air, Ecotoxicity, Human health particulate air, Human toxicity cancer and non-cancer, Resources fossil fuels and Smog air.